Compreensão da problemática da periferização por segregação involuntária no planejamento da acessibilidade e mobilidade em Fortaleza - Andrade, Beatriz Rodrigues (2016)
The phenomenon of the peripheralization, one of the largest urban problems today, restricts the share of the population that lives in urban fringes to actively participate in the Urbis as an area of social, political and economic exchanges, that is, directly impacts in the accessibility of people to activities they want accomplish in urban space. Depending on the amount and intensity of the restrictions imposed on a group disability in their levels of accessibility and mobility can generate a scenario of social exclusion, which makes the low-income population that inhabits the periphery (involuntary segregation) a risk group. In this master's research, to achieve the overall objective to understand the marginal involuntary segregation in Fortaleza through of the integrated problematic modeling, benefited from a necessary systematization of integrated planning process of accessibility and urban mobility, that is highlighted in three areas: theoretical and conceptual (through conceptual model ALUTI), methodological and operational. Considering the complexity of the studied phenomenon, to systematize operationally problematic and assist primarily in the diagnosis stage (prognosis and assessment scenario), the computing platform TRANUS was used, which bolstered the modeling of the indicators used to characterize involuntary peripheralization and diagnose the causal links between this problem, that is embodied in the subsystem of land use, and levels of accessibility and mobility of low population income living in these conditions segregation.